What motivates people with type 2 diabetes mellitus to participate in clinical trials from home? - Julia Kopanz; Bart Lagerwaard; Magdalena Beran; Jorien Veldwijk; Julia K. Mader; Tina Pöttler; Dietrich Tews; Diederick E. Grobbee; Mira G. P. Zuidgeest; the Trials@Home consortium (Wiley, 2024)
Abstract Decentralized clinical trials (DCTs), in which all or part of the trial activities are moved to the participants' immediate surroundings, promise to improve trial conduct. However, no evidence is available on what motivates people to participate in DCTs. Our aim was to determine the drivers and perceptions for participation in clinical trials with different decentralization levels in persons with type 2 diabetes mellitus. Five focus groups were conducted utilizing the nominal group technique in the Netherlands (n = 1), Germany (n = 1), and Austria (n = 3) with four to six participants per group. The focus groups were analyzed using thematic analysis. Of the 26 participants (10 females, median age: 66 years [IQR: 62-72]) 42% had previously participated in a trial, and almost all had internet access at home (96%). A total of seven main themes regarding participation in clinical trials (location, time investment, contact with healthcare professionals (HCPs), digital technologies, data collection, perceived risk, and motivation) were identified, of which a total of 20 drivers emerged. Perceptions regarding trial participation differed widely among participants, and individual preferences influenced which drivers were considered more important by participants. Flexibility of location and time spent on the trial were identified as the most motivating factors for participation in DCTs. Some drivers, such as digital infrastructure, digital literacy, home visits, personal interaction, and relationship with HCPs were perceived as both enablers and barriers, depending on personal preferences. However, most of the potential barriers regarding DCTs may be resolved by addressing them in the design of future DCTs.